Foreign Wage Premium, Gender and Education : Insights from Vietnam Household Surveys - Fukase, Emiko (World Bank, Washington, DC, 2013)
This paper investigates the differential impacts of foreign ownership on wages for different types of workers (in terms of educational background and gender) in Vietnam using the Vietnam Household Living Standards Surveys of 2002 and 2004. Whereas most previous studies have compared wage levels between foreign and domestic sectors using firm-level data (thus excluding the informal sector), one advantage of using the Living Standards Surveys in this paper is that the data allow wage comparison analyses to extend to the informal wage sector. A series of Mincerian earnings equations and worker-specific fixed effects models are estimated. Several findings emerge. First, foreign firms pay higher wages relative to their domestic counterparts after controlling for workers personal characteristics. Second, the higher the individual workers' levels of education, the larger on average are the wage premiums for those who work for foreign firms. Third, longer hours of work in foreign firm jobs relative to working in the informal wage sector are an important component of the wage premium. Finally, unskilled women experience a larger foreign wage premium than unskilled men, reflecting the low earning opportunities for women and a higher gender gap in the informal wage sector.